Identification of CNOT1-CCR4-NOT as a suppressor of 53BP1-p53-p21 signaling - Antonio Galarreta; Virginia Pasti; Julia Vornberger; Ralph Imhof; Mariano Oppikofer; Matthias Altmeyer (Cell Reports)
Summary: Tumor suppressor p53 has inherent propensities to self-associate, which can lead to oncogenic p53 aggregation. The genome caretaker 53BP1 interacts with p53, forms DNA damage-associated condensates, and has been implicated in p53 activation. Modulating the balance between functional p53 self-association and dysfunctional aggregation may restore tumor-suppressive functions of p53 in cancers with otherwise dampened p53 activity. Here, we identify cellular regulators of 53BP1-p53 signaling based on multi-dimensional high-content microscopy screens using nuclear p53 levels and 53BP1-p53 condensates as primary readouts. Through orthogonal validation, carbon catabolite repression 4 (CCR4)-negative on TATA-less (NOT) transcription complex subunit 1 (CNOT1) emerges as a suppressor of 53BP1-p53-p21 signaling. Consequently, depletion of CNOT1 impairs proliferation, induces apoptosis, and causes cancer cell death. CNOT1 interacts with 53BP1 and impacts its nuclear dynamics, and CNOT1 loss upregulates p53 target gene expression. Finally, we demonstrate that CNOT1 loss suppresses cytoplasmic aggregation of mutant p53, thereby restoring nuclear localization and functionality of p53 mutants frequently found in cancer.